A Review of Etlingera coccinea (Blume) S. Sakai and Nagam (Zingiberaceae) on Achievement of Producing an Essential Oil and Medicinal Properties in Sabah, East Malaysia - Emmeldah Joseph; Elia Godoong (Universiti Malaysia Sabah, 2023)
The wild ginger, Tuhau, E. coccinea is a plant species from Etlingera genus and Zingiberaceae family. This study is focused on a reviewed paper reported on the extraction method used to derive essential oils and the overview of the published data regarding medicinal properties of Etlingera coccinea spp. The search was performed in several databases such as ScienceDirect, Scopus, SpringerLink, and Research gate and also Google Scholar. The following keywords were used individually and or in combination “E. coccinea” and “Tuhau”. This article highlights the extraction techniques used to derive the essential oil of E. coccinea and also provide briefly overview of the medicinal properties from the data in recent literature.